Dialog Ayah Dan Anak Dalam Al-Qur’an: Analisis Tafsir Maqashidi Terhadap Fenomena Fatherless - Zahrotun Zahrotun, Mohammad Khoiril Anwar (Al-Qudwah)
This article aims to explore the forms of paternal parenting dialogues in Surah Luqman: 13 and Surah Ash-Shaffat: 102, along with the wisdom behind the use of the term 'father' (ayah). Additionally, the researcher aims to identify the maqashid values within these two verses to address the phenomenon of fatherlessness. Fatherlessness has become a hotly discussed issue in the context of parenting, considering the increasingly modern family conditions, economic pressures, and the marginalized role of fathers as primary educators. The research method employed is thematic (maudhu'i) exegesis with a maqashidi approach. The issues to be addressed include the forms of dialogue between fathers and children in the Qur'an and the phenomenon of fatherlessness from a maqashidi exegesis perspective. The research results indicate that the phenomenon of fatherlessness contradicts the ideal role of a father as explicitly depicted in the stories of Luqman and Prophet Ibrahim in the Qur'an. The paternal role consists of three levels: biological, material provision, and loyalty. However, various factors, including economic, social, and personal emotional aspects, may hinder optimal functionality. In alignment with the understanding of the paternal role, the fatherlessness phenomenon in millennial family life can be minimized. Fathers need to recognize that, in addition to their role in meeting material needs, they play a crucial part in shaping the character and future of their children. The maqashid from Surah Luqman 13 and Surah Ash-Shaffat 102, depicting paternal dialogue, emphasize his responsibility in parenting, addressing the fatherless phenomenon, encompassing six primary maqashid, especially hifzh ad-din (preservation of religion) and hifzh al-nasl (preservation of lineage).